PELAKSANAAN YOGA PRENATAL TERHADAP KUALITAS TIDUR PADA IBU HAMIL TRIMESTER III DI PMB SUKMAWATI,S.ST.M.KES - Lili Purnama Sari; Dahniar Dahniar (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2021)
AbstractDiscomfort during pregnancy will interfere with sleep quality which will have an impact on psychological disorders during pregnancy. Objective: To see the effect of the implementation of prenatal yoga on the sleep quality of third trimester pregnant women. Research Method: Experiment with One Group Pretest-Postest Design. Sampling was done by total sampling technique and a sample of 30 respondents. The instrument used is a questionnaire. Data analysis using SPSS program with Paired Simplet T Test statistical test. Results: the results of the analysis of the effect of prenatal yoga on sleep quality obtained with a value of = 0.000, meaning that there is an effect of the implementation of prenatal yoga on the sleep quality of pregnant women in the third trimester. Research implications: Prenatal yoga intervention can improve sleep quality, thereby reducing complaints in third trimester pregnant women. Recommendation: It is hoped that there will be research that intervenes in prenatal yoga for pregnant women in the third trimester to reduce anxiety and other complaints including insomnia and low back pain in pregnant women.